THIRD CULTURE KID’S EFFECT ON CHARACTER OF CADY HERON IN MEAN GIRLS - Hapsari, Laily (LANTERN (Journal on English Language, Culture and Literature), 2017)
This thesis focuses on the movie, Mean Girls, specifically one of the character, Cady Heron,as a Third Culture Kid trying to adapt in new society. The purpose of this study is to understand the effect of Third Culture Kid in the movie character in socializing with the new surroundings and explain the way how one of the characters in Mean Girls adapts to the new surroundings.The writer uses library research to collect the data with the novel as the main data, and several relevant books, journals, articles, also online documents and websites are used as the supporting data. The intrinsic aspects cover characters, setting, and conflicts. In the extrinsic aspect, the writer uses Irwin Altman and Dalmas Taylor’s Social Penetration Theory whichis applied in the thesis to analyze the problem. The result of this thesis proves that according to Irwin Altman and Dalmas Taylor’s Social Penetration Theory, Cady Heron uses her Third Culture Kid context to evade social isolation whilst preserving her identity through several roles in adapting in the new surroundings.